Arteriovenous malformation embocure score: AVMES. (15th June 2015) - Lopes, Demetrius K; Moftakhar, Roham; Straus, David; Munich, Stephan A; Chaus, Fahad; Kaszuba, Megan C
Abstract : Background: Cerebral arteriovenous malformations (CAVMs) may be treated with microsurgery, radiosurgery, endovascular surgery, or a combination of these modalities. Grading scales are available to aid the assessment of curative risk for microsurgery and radiosurgery. No grading system has been developed to assess the curative risk of endovascular surgery. Objective: To report our retrospective application of the AVM embocure score to patients treated at our institution between 2005 and 2011 Methods: We performed a retrospective review of 39 patients with CAVM treated at our institution between 2005 and 2011 with the primary aim of achieving a curative embolization. After reviewing all the different variables associated with the conventional Onyx embolization technique for CAVMs, we identified the following as the most relevant characteristics influencing the chances for complete angiographic embolization and complication risk: the number of arterial pedicles and draining veins, size of AVM nidus, and vascular eloquence. We sought to develop a scoring system to assess the complication risk for a curative embolization of CAVM with liquid embolic Onyx (Covidien, Irvine, California, USA). We developed the AVM embocure score (AVMES). This scoring system ranges from 3 to 10 and is the arithmetic sum of the number of arterial pedicles feeding the AVM (≤3, 4–6, >6), the number of draining veins (≤3, 4–6, >6), the size of the AVM nidus in centimeters (≤3, 4–6, >6), and the vascular eloquence (0–1). We applied AVMES to the same cohort of patients and validated the predictability of complete angiographic embolization and expected clinical risk of complication. Results: In lesions with an AVMES of 3 (n=8), there was a 100% rate of complete AVM obliteration and 0% rate of major complications. In AVMES 4 (n=12) lesions, there was 75% complete obliteration rate, with 8% major morbidity. In AVMES 5 (n=9) lesions, there was 78% complete obliteration and 11% major morbidity. In AVMES >5 (n=10) there was 20% complete obliteration and 30% major morbidity. Receiver-operator curve analysis showed that this scoring system was robust in its discriminative ability, with an area under the curve (AUC) of 0.8356 for complete obliteration without complication, AUC=0.8240 for complete obliteration regardless of the presence of major morbidity, and AUC=0.7529 for major morbidity. Conclusions: The AVMES complements existing scoring systems for microsurgery and radiosurgery. It provides a valuable tool for risk assessment during the complex decision-making process in treating AVMs that accounts for angioarchitectural features of particular relevance to endovascular surgeons.